Tat}biq Bi>ah Lughawiyah li Tah}si>n Maha>rah al Kala>m Fi> Ma’had “ H{amalatul Qur’a>n” Bandung Diwek Jombang - Muhammad Maksum Ali; Burhanuddin Ubaidillah (EL-FUSHA: Jurnal Bahasa Arab dan Pendidikan, 2024)
The linguistic environment is one way to learn Arabic by creating a special area where everyone speaks the same language. This method is applied at the Hamalatul Qur'an Islamic boarding school located in the village of Bandung, Diwek, Jombang. The main purpose of applying this method is to improve speaking skills, namely the ability to convey ideas, information or messages orally correctly and clearly using Arabic. This study aims to find out what the application of the language environment method is like in the effort to learn language skills. The research method used is field research with a qualitative approach. The results of this study show the application of the linguistic environment in efforts to learn speaking skills and research that the use of linguistic environment methods can create habituation so that students can memorize, remember and pronounce Arabic more easily and correctly..